Penerapan Artificial Intelligence ( AI ) Dalam Pelayanan Publik Berbasis E- Government - Aulia Tasya; Ifandra Syaputra; Nayla Fatiya Zalvi; Boni Saputra; M. Fachri Adnan (CV. ITTC INDONESIA, 2026)
Public services in Indonesia currently face various challenges, such as complex bureaucratic processes, low service efficiency, and the suboptimal use of digital technology to support governance. These conditions drive the need for innovation through the application of Artificial Intelligence (AI) in e-government systems to improve the quality of public services. This study aims to analyze the role of AI in transforming the orientation of public services from an administrative and reactive system to a more predictive, responsive, and data-driven one. The study employed a literature review method, examining relevant literature on AI, e-government, and public services published between 2020 and 2026. Data were collected through a literature review and analyzed using descriptive-qualitative analysis techniques by identifying, comparing, and synthesizing findings from previous research. The results show that the application of AI in e-government-based public services can improve the effectiveness, efficiency, transparency, and responsiveness of services through process automation, faster data management, and support for data-driven decision-making. However, its implementation still faces various challenges, such as limited digital infrastructure, human resource quality, data security, and regulations that do not fully support the use of AI. Therefore, it is necessary to strengthen infrastructure, increase the capacity of the apparatus, and adopt adaptive policies so that the use of AI can support the realization of more modern and quality public services.